PENDIDIKAN SAINS DAN TEKNOLOGI BERBASIS TEORI KONEKTIVISME DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Ii Rahmanudin (Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
The application of science and technology in education has two objectives. First, for the learning process activities. Second, to support administrative activities, namely the management of the education system concerned. Connectivism theory is considered a new learning theory that emphasizes interactive learning in online (online) contexts. There are four types of activities that can support connectivism learning theory, namely: aggregation, relations, creation, and sharing. Critical thinking helps students to evaluate what students learn in class. The purpose of developing students' critical thinking skills is because when students are able to think critically students can decide what to believe or do. The implications of connectivism learning theory in science and technology learning that uses digital are currently quite large to feel its influence on the development of students' critical thinking, especially in terms of student interpretation, student analysis, evaluative students, and student decision making. So the purpose of this study is to find out how Science and Technology Education Theory of Connectivism in developing students' critical thinking skills. This research uses a descriptive qualitative method with a library research approach. The data collection technique is by collecting data related to the theory of connectivism and critical thinking and analyzing the data using content analysis.